2009
DOI: 10.1002/hep.22848
|View full text |Cite
|
Sign up to set email alerts
|

Increased intestinal permeability and tight junction alterations in nonalcoholic fatty liver disease

Abstract: The role played by the gut in nonalcoholic fatty liver disease (NAFLD) is still a matter of debate, although animal and human studies suggest that gut-derived endotoxin may be important. We investigated intestinal permeability in patients with NAFLD and evaluated the correlations between this phenomenon and the stage of the disease, the integrity of tight junctions within the small intestine, and prevalence of small intestinal bacterial overgrowth (SIBO). We examined 35 consecutive patients with biopsy-proven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
991
3
28

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 1,225 publications
(1,075 citation statements)
references
References 45 publications
(48 reference statements)
21
991
3
28
Order By: Relevance
“…Moderate alcohol drinking might have a protective role on the risk of developing NAFLD in view of the (Dunn et al 2008) or through the beneficial effect of high-density lipoprotein (HDL) cholesterol increased levels as for cardiovascular disease (CVD) (Djousse et al 2009). Additional studies, however (Abdelmalek et al 2010;Abid et al 2009), suggested that a high intake of soft drinks which are rich of fructose, might have a detrimental effect on the risk of NAFLD (Miele et al 2009). In our study, the information on alcohol, however, was limited to wine and spirits consumption, thus did not include information on soft drinks consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate alcohol drinking might have a protective role on the risk of developing NAFLD in view of the (Dunn et al 2008) or through the beneficial effect of high-density lipoprotein (HDL) cholesterol increased levels as for cardiovascular disease (CVD) (Djousse et al 2009). Additional studies, however (Abdelmalek et al 2010;Abid et al 2009), suggested that a high intake of soft drinks which are rich of fructose, might have a detrimental effect on the risk of NAFLD (Miele et al 2009). In our study, the information on alcohol, however, was limited to wine and spirits consumption, thus did not include information on soft drinks consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is evidence that hepatic inflammation can be reduced by means of changes to the gut microbiota induced by antibiotics and probiotics. [47][48][49][50][51][52][53][54][55][56] Under high levels of oxidative stress, which is a feature usu- …”
Section: Pathophysiologymentioning
confidence: 99%
“…On the other hand, the components of MS, such as hypertriacylglycerolaemia, hyperglycaemia and hyperinsulinaemia, are hypothesized to contribute to endotoxaemia through altering jejunal motility and gastrointestinal transit time, conditions that may favor bacterial overgrowth, and leak endotoxins into the intestinal mucosa [71]. This might also explain the increased prevalence of SIBO in NAFLD patients, as reported by our group [25]. Other studies also find that obese individuals have significantly higher LBP levels compared with their normal-weight counterparts [72].…”
Section: Nalfd: the Liver At The Centermentioning
confidence: 54%
“…In in vitro and animal models of NAFLD, increased IP, and alterations of gut microbiota have been shown to increase the exposure of the liver to gut-derived bacterial products [such as lipopolysaccharides (LPS)], which may cause low-grade endotoxemia in the portal system [24]. Both IP and the prevalence of SIBO appear to be correlated with the severity of steatosis [25]. Bacterial products belong to distinct classes of endogenous signals, triggering the host immune response by the activation of Toll-Like Receptors (TLRs) [26].…”
Section: Nalfd: the Liver At The Centermentioning
confidence: 99%
See 1 more Smart Citation